2016
DOI: 10.1097/mpg.0000000000001093
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Maternal Microchimerism in Regional Lymph Nodes of Children With Biliary Atresia

Abstract: This result challenges the hypothesis that maternal cells play a role in hilar lymphadenopathy of children with BA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…Our data are consistent with the results of qPCR-based analyses of other tissues; Nelson et al identified maternal microchimerism in four of 24 blood samples of healthy children with the estimated number of maternal cells per 10 6 total cells ranging from 0 to 79 (11). In this regard, while Engelmann et al (7) did not detect maternal cells in any of the five liver lymph node samples obtained from patients with BA, this can be explained by the relatively high limit-of-detection of that study (0.1% maternal cells in total cells).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data are consistent with the results of qPCR-based analyses of other tissues; Nelson et al identified maternal microchimerism in four of 24 blood samples of healthy children with the estimated number of maternal cells per 10 6 total cells ranging from 0 to 79 (11). In this regard, while Engelmann et al (7) did not detect maternal cells in any of the five liver lymph node samples obtained from patients with BA, this can be explained by the relatively high limit-of-detection of that study (0.1% maternal cells in total cells).…”
Section: Discussionsupporting
confidence: 91%
“…The frequency and quantitative levels of maternal microchimerism were comparable between the BA and control groups. These results, in conjunction with those of the previous study by Engelmann et al using liver lymph node samples (7), argue against a major role of maternal microchimerism in the etiology of BA. In this regard, recent studies have cast doubt on the etiological relationship between maternal microchimerism and various autoimmune disorders (15–17).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The lack of an identifiable genetic cause of BA has led to the hypothesis that maternal microchimerism (postzygotic somatic mutation) may be part of the etiology 17, 18 . Although a recent study has shown no evidence of maternal microchimerism in lymph nodes 19 , additional studies would be required to both demonstrate the presence of microchimerism in BA and show that it has a causal role in the disease.…”
Section: Genetic Susceptibility In Biliary Atresiamentioning
confidence: 95%